Groundwater Management in Balochistan, Pakistan : A Case Study of Karez Rehabilitation - Ashraf, Muhammad (World Bank, Washington, DC, 2020)
Balochistan is an arid region with limited and seasonal surface water resources. It is also home to the ancient Karez water supply system that has long served as a buffer against droughts. About one-third of the 3,000 such systems that were believed to be in place in 1970 are still functioning. Aside from its cultural and historical significance, the Karez system has helped transform the agrarian landscape of the uplands, improving socioeconomic conditions. However, recurring droughts since the 1960s resulted in reduced recharge to groundwater supporting the Karez systems at a time of growing demands. To maintain their livelihoods, farmers installed tubewells, aided by energy subsidies from the provincial government.